Decoding consumer-centric transition to electric mobility based on sentiment, semantic and statistical analysis - Pani A.; Balla S.N.; Sahu P.K. (My University, 2025)
Climate change, carbon emissions, and energy resource depletion have become major concerns worldwide. The transportation sector is a primary target in various political and environmental agendas to tackle them. This calls for switching to sustainable transportation, and one of the important steps towards it is vehicle electrification. Understanding public attitudes towards electric vehicles (EVs) is the key to escalating vehicle electrification. By doing so, governments and enterprises can take the necessary action to persuade people to adopt electric mobility. Unlike past studies, which measured public attitudes using user acceptance data at a minuscule level, this paper adopts a macroscopic approach to this problem by mining public opinions from Twitter. Since Twitter provides access to its public tweet database, decoding the opinions of a vast population for extensive periods has become computationally tractable in recent years. The collected tweets have been used to examine the temporal and geographical dimensions of public perception using Natural Language Processing techniques. The substantial shifts in public sentiment have been identified, and the underlying incidents and topics were interpreted. In the pre-pandemic phase, most of the study nations saw an improvement in public sentiment towards EVs in the time period just before the COVID-19 pandemic, which can be attributed to the world-wide race to zero emissions to meet the Paris Agreement's carbon reduction targets. The public optimism further improved during the pandemic period. After the pandemic, the positivity towards EVs has declined in majority of the nations. The interpreted topics of discourse at the sentiment changepoints can be categorised into the following broad themes: (i) users and potential customers discourse, (ii) engineering and technology, (iii) politics, (iv) environment, (v) business and marketing, and (vi) miscellaneous. Most of the topics of discussion were centred around electric automotive firms, signifying the importance of the role of electric vehicle enterprises in electric vehicle adoption. The outcomes of this study can aid policymakers and electric automotive firms in comprehending the evolution of public perception towards electric mobility and thereby adopt and accelerate the human-centric transitions to carbon-neutral transport options. © 2023 Elsevier Ltd